The Influence of Leadership Style and Work Decisions on Employee Performance At PT. Indah Sakti - Harnona (Jurnal Manajemen Bisnis Eka Prasetya, 2022)
This study aims to analyze the effect of leadership style and job satisfaction on the performance of employees of PT. Beautiful Sakti. The sample in the study were all employees of the company as many as 105 employees of PT. Beautiful Sakti. The data analysis model used in this study is a multiple regression analysis model. The results showed that based on the data and analysis results obtained from research that has been done by the author at PT. Indah Sakti, namely, the first hypothesis is accepted, namely the results of the study indicate that the leadership style variable partially has a positive and significant influence on employee performance at PT. Beautiful Sakti. The second hypothesis is accepted, namely the results of the study indicate that the job satisfaction variable partially has a positive and significant influence on employee performance at PT. Beautiful Sakti. The third hypothesis is accepted, namely the results of the study indicate that the variables of leadership style and job satisfaction simultaneously have a positive and significant influence on employee performance at PT. Beautiful Sakti.